Die abjekte held in Steppenwolf, Fight Club en a Whistling Woman : Kielhaal (roman) - Kapp, T. P. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MA (Afrikaans and Dutch))--University of Stellenbosch, 2006.